The question involves finding the solution to a partial differential equation.

The general solution that I found was $u(x,t)=F(x^{2}-t^2 e^{u})$ and the initial condition is $u(x,0)=2\ln (x)$. The issue I've been having is trying to apply that data to the general form.

What I tried was plugging in the data to the general solution to get: $2\ln (x) = F(x^{2})$ From there I let $x^{2} = z$ and hence $x=\sqrt{z}$, which gives me: $2\ln(\sqrt z ) = F(z)$

and then I tried taking this and subbing it through to the original solution I had, which gives:

$u(x,t) = 2\ln (\sqrt{x^{2}-t^2e^{u}})$

The solution to the problem is $u(x,t) = \ln (\frac{x^{2}}{1+t^{2}})$, was wondering if anyone could help point out what i did wrong.

Original PDE is $\partial_t u + \big(\frac{t}{x}e^u\big)\partial_x u = 0$ (see problem statement).


If you use the logarithm laws, $a\ln b=\ln( b^a)$, you find that $F(x^2)=\ln(x^2)$, thus $F(z)=\ln z$ and with that $$ u=\ln(x^2-t^2e^u)\implies e^u=x^2-t^2e^u\implies e^u=\frac{x^2}{1+t^2}. $$


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.